Self-Powered Balun Low Noise Amplifier with Degeneration Balancing and Thermal Noise Analysis - Abubaker, Qusai Mohammad (2020)
A Master of Science thesis in Electrical Engineering by Qusai Mohammad Abubaker entitled, “Self-Powered Balun Low Noise Amplifier with Degeneration Balancing and Thermal Noise Analysis”, submitted in May 2020. Thesis advisors is Lutfi Albasha. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form). Embargo expires February 25, 2021.